Genome inheritance in populations derived from hexaploid/tetraploid and tetraploid/hexaploid wheat crosses - Padmanaban, Sriram; Sutherland, Mark W.; Knight, Noel L.; Martin, Anke (Molecular breeding, 2017)
Hexaploid/tetraploid and tetraploid/hexaploid wheat hybrids were established using the hexaploid ( Triticum aestivum L.) bread wheat LRC2010-150 and the tetraploid durum wheat ( T. turgidum spp. durum ) WID802. Thirty F 2 progeny from each cross were characterised using Diversity Arrays Technology (DArTseq™) markers to determine whether there are differences between the crosses in the proportion of A, B and D genomic material inherited from each parent. Inheritance of the A and B genome from the tetraploid durum parent varied from 32 to 63% among the 60 lines assessed, and results indicated significant differences between the two F 2 populations in the mean overall proportion of chromosomes A and B inherited from each parent. Significant differences were also observed between the crosses in the proportion of chromosomal segments on 2B, 3A, 3B and 4A inherited from the tetraploid parent. The F 2 populations also showed significant differences in the average retention of D chromosomes per line with the tetraploid/hexaploid cross retaining a mean of 2.83 chromosomes while the reciprocal cross retained a mean of 1.8 chromosomes per line. A strong negative correlation was observed in individual lines from both populations between the proportion of the A and B genome inherited from the tetraploid durum parent and the retention of the D genome. The implication of these results for the design of efficient crossing strategies between hexaploid and tetraploid wheats is discussed.